Contraction Type Expansive Map on Complex Valued Metric Space with Fixed Points - Tiwari, Surendra Kumar; Sonant, Bindeshwari; Sahani, S.K. (Darul Yasin Al Sys, 2023)
According to the present paper, the two self mappings that satisfy contraction type conditions of expansive in complete complex valued metric space reveals that these mappings have some common fixed points. Furthermore, the paper provides generalizations and extensions of well-known results from the existing literature which further expands our understanding of this topic. Some illustrative examples are given to help us obtain results.